Unsur-Unsur Intrinsik Cerita Mahabharata dalam The Mahabharata Karya R.K. Narayan - Dewi Nurnani (Institut Seni Indonesia Surakarta, 2021)
The article entitled “The Intrinsic Elements of the Mahabharata Story in the Book of The Mahabharata by R.K. Narayan” examines how the intrinsic elements contained in the Indian novel by R.K. Narayan entitled The Mahabharata. This study uses a qualitative descriptive method with a literary approach through the study of the intrinsic elements of Nurgiyantoro. Data were obtained through literature study and direct interviews with puppet experts or puppeteers. The results of this study indicate that there are events, conflicts, and climaxes in the Mahabharata storyline with traditional themes, physical and spiritual settings, as well as protagonists and antagonists characters.